A Modified Method for Consistent and Reliable Golgi–Cox Staining in Significantly Reduced Time - Ranjan, Amit; Mallick, Birendra N. (Frontiers in Neurology, 2010)
The two major limitations of Golgi-Cox method are that staining takes very long time and it is inconsistent. In this paper we describe a modification of the Golgi-Cox method, in which the tissue blocks were maintained at 37 ± 10C during chromation for only 24 hours and consistent staining of neurons in rat brain sections were observed. The method is simple, reproducible, rapid, inexpensive and provides uniform staining with very good resolution of neuronal soma, dendrites as well as spines.